SAT0429 SECUKINUMAB IMPROVES CLINICAL AND PATIENT-REPORTED OUTCOMES AT 6 MONTHS AMONG PATIENTS WITH PSORIATIC ARTHRITIS IN THE US-BASED CORRONA PSORIATIC ARTHRITIS/SPONDYLOARTHRITIS (PsA/SpA) REGISTRY. (2nd June 2020) - Mease, P. J.; Blachley, T.; Glynn, M.; Dube, B.; Mclean, R.; Kim, N.; Hur, P.; Ogdie, A.
Abstract : Background: Secukinumab, an interleukin-17 antagonist approved for the treatment of PsA, improves all PsA manifestations in the GRAPPA-OMERACT core domain set. 1 Few US-based studies have evaluated the real-world effectiveness of secukinumab in patients with PsA. Objectives: To examine clinical and patient-reported outcomes (PROs) in patients with PsA enrolled in the Corrona PsA/SpA registry initiating secukinumab with ≥ 1 follow-up visit. Methods: Included were adult patients with PsA in the Corrona registry who initiated secukinumab after April 1, 2017 and remained on secukinumab at their 6-month (window, 5-8 months) follow-up visit. The primary outcome was achievement of minimal disease activity (MDA) at 6 months among patients not in MDA at secukinumab initiation. MDA was defined as meeting 5 of the 7 following criteria: tender joint count (TJC) ≤ 1, swollen joint count (SJC) ≤ 1, psoriasis affected body surface area (BSA) < 3%, patient assessment of pain on visual analog scale (VAS) ≤ 15, patient global assessment VAS ≤ 20, HAQ-DI ≤ 0.5, and tender entheseal points ≤ 1 using the Leeds Enthesitis Index (LEI). Secondary outcomes included the proportion of patients who achieved resolution (0 sites) of TJC, SJC, enthesitis (using the LEI), and dactylitis among those with ≥ 1 site at initiation and improvement from baseline in clinical outcomes (BSA, nail psoriasis, physician global assessment, TJC, SJC, and DAPSA) and PROs (patient-reported pain, patient global assessment, HAQ-DI, and Work Productivity and Activity Impairment questionnaire) at 6 months. Outcomes were evaluated in the overall population and in potentially recalcitrant patients with failure of or intolerance to ≥ 3 previous biologics to examine if the later line biologic could be adequately effective. Results: A total of 100 patients with PsA who initiated and maintained secukinumab after 6 months were included. The mean (SD) age was 51.6 (11.6) years, 54.3% were male, and 96.8% were white. The mean (SD) symptom and disease duration were 10.8 (9.7) and 7.0 (7.0) years, respectively. Thirty patients (30.0%) initiated secukinumab 150 mg and 70 (70.0%) initiated secukinumab 300 mg. Most (83.0%) were biologic experienced; 17 patients initiated secukinumab as a 1st biologic, 34 as 2nd, 26 as 3rd, and 23 as ≥ 4th. At initiation, 75/90 patients (83.3%) were not in MDA; 26/71 (36.6%) of those with follow-up data available achieved MDA at 6 months (Figure 1 ). In the overall population, 28 patients (41.2%) with TJC ≥ 1, 24 (44.4%) with SJC ≥ 1, 17 (60.7%) with enthesitis, and 9 (75.0%) with dactylitis at initiation achieved resolution at 6 months (Table 1 ). Improvement was observed at 6 months in clinical outcomes and PROs in the overall population (Figures 1 and 2 ) and in patients who initiated secukinumab as a ≥ 4th-line biologic. Conclusion: In the Corrona registry, most secukinumab initiators with PsA were biologic experienced and were not in MDA at time of initiation. Consistent with clinical trials, real-world patients treated with secukinumab achieved MDA as well as improvement in clinical manifestations, PROs, and work productivity. References: [1]Orbai AM, et al. J Rheumatol. 2019 Oct 15. [Epub ahead of print]. Disclosure of Interests: Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Taylor Blachley Employee of: Corrona, LLC, Meghan Glynn Shareholder of: Corrona, LLC – shareholder, Grant/research support from: Pfizer – grant/research support, Employee of: Corrona, LLC – employment, Blessing Dube Employee of: Corrona, LLC, Robert McLean Employee of: Corrona, LLC, Nina Kim Employee of: Postdoctoral fellow at the University of Texas at Austin and Baylor Scott and White Health, providing services to Novartis Pharmaceuticals Corporation, Peter Hur Employee of: Novartis Pharmaceuticals Corporation, Alexis Ogdie Grant/research support from: Pfizer to Penn, Novartis to Penn, Amgen to Forward/NDB, Consultant of: Abbvie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Janssen, Eli Lilly, Novartis, Pfizer